Design and experiment of the key components of the seeding monomer for high-speed corn no-till seeders - Chen, Yongliang; Jing, Hairong; Zhang, Zhe; Guo, Yuhang; Ning, Xiaofeng (International Journal of Agricultural and Biological Engineering, 2023)
Aiming at the problems of uneven plant spacing, row spacing and sowing depth due to the collision of seeds with the tube wall or bouncing on the floor of the seed guide tube with the increase of operation speed of the current corn no-till planter, in this study, the high-speed seed belt technology was combined with the finger clip seed discharge device, a kind of high-speed no-till planter monomer was designed and installed in high-speed seed tube. At the same time, simulation analysis was made on the movement law of seeds in the seed guide tube when they fell from the finger clip seeder and the main structural parameters and the range of key parameters of the high-speed seed tube were determined. Through the prototype, the single-factor and quadratic orthogonal rotational combination test method, and the machine operating speed, the height of the high-speed seed tube and the seed guide angle were selected as the test factors in the seeding performance test. After parameter optimization, the optimal working parameters were determined: the machine forward speed was 12.18 km/h, the height of the high-speed seed tube from the ground was 42.22 mm, and the seed guide angle of the high-speed seed tube was 8.82°. The field test verified that under this parameter combination, the qualified-seeding index was 94.95%, the multiple-seeding index was 2.37%, and the missing-seeding index was 2.48%, showing stable working performance and satisfied the sowing and agronomic requirements of the no-till seeding operation. Keywords: no-till planter, seeding monomer, high-speed seed tube, field test DOI: 10.25165/j.ijabe.20231605.7687 Citation: Chen Y L, Jing H R, Zhang Z, Guo Y H, Ning X F. Design and experiment of the key components of the seeding monomer for high-speed corn no-till seeders. Int J Agric & Biol Eng, 2023; 16(5): 95–103.